The hybrid of PTS-CAPPR methods with MA for PAPR reduction in OFDM systems - Pradabpet, Chusit; Chivapreecha, Sorawat; Yimman, Surapan (My University, 2013)
The hybrid of partial transmit sequences (PTS) and cascade adaptive peak power reduction (CAPPR) methods have been used to reduce peak to average power ratio (PAPR) of orthogonal frequency division multiplexing(OFDM) system. When number of sub-block increases, PAPR is getting small. However, the calculation cost of its selection must be considerably large. W e introduce memetic algorithm(MA), the total calculation cost becomes drastically reduced. The parameter for simulation used standard WLAN in IEEE 802.11a system. In simulation results, the proposed method shows the improvement performance PAPR, bit error rate (BER) and power spectrum density (PSD) of an OFDM system. © 2013 IEEE.
Keywords: CAPPR; MA; OFDM; PAPR; PTS